THE ROLE OF THE PRODUCER IN THE PRODUCTION OF THE FEATURE PROGRAM 'BACKSTAGE' EPISODE 'BEHIND THE SCENES OF THEATER ARTS - Bumi Respati, Moehamad Gentar; Irawan, Rahmat Edi (Transpublika Publisher, 2023)
This